2023
DOI: 10.3389/fendo.2023.1210943
|View full text |Cite
|
Sign up to set email alerts
|

Warthin-like papillary thyroid carcinoma: a case report and comprehensive review of the literature

Abstract: BackgroundPapillary Thyroid Carcinoma (PTC) is the most frequent endocrine malignancy with a variety of histological presentations. Warthin-like Papillary Thyroid Carcinoma (WLPTC) is an uncommon neoplasm that is recognized as a distinct subtype of PTC in the WHO classification of thyroid tumors. In this report, we present a novel case of WLPTC in a female patient and provide an in-depth review of the available literature on its clinical, pathological, and therapeutic characteristics.Case presentationA 27-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The cytological pattern of the WLV-PTC can imitate distinct pathologies, such as: Hurtle cell carcinoma, oncocytic variant of PTC, lymphocytic thyroiditis and follicular lesion [ 12 ]. Missaoui et al examined 150 patients with WLV-PTC who made up 87.5% Bethesda categories 5 and 6 [ 3 ]. The result of FNA of the presented patient was Bethesda category 6 (malignant).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytological pattern of the WLV-PTC can imitate distinct pathologies, such as: Hurtle cell carcinoma, oncocytic variant of PTC, lymphocytic thyroiditis and follicular lesion [ 12 ]. Missaoui et al examined 150 patients with WLV-PTC who made up 87.5% Bethesda categories 5 and 6 [ 3 ]. The result of FNA of the presented patient was Bethesda category 6 (malignant).…”
Section: Discussionmentioning
confidence: 99%
“…We represent a case of such as a unique subtype of PTC as the Warthin-like variant obtained by 40-year-old woman. In the vast majority of cases, a tumor is diagnosed in women aged 30 to 50 [ 3 ]. Kim et al revealed 0.2% presence of the Warthin-like variant of papillary thyroid carcinoma (WLV-PTC) in 8179 patients [ 4 ].…”
Section: Introductionmentioning
confidence: 99%